THE ROLE OF NUTRITION IN THE GROWTH AND DEVELOPMENT OF YOUNG PEOPLE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Growth and development are complex processes that require the right balance of nutrients. Growth refers to dimensional growth such as height and weight, while development refers to the acquisition of attitudes, behaviors, and social skills. It will be discussed about the role of nutrition in the growth and development of young people.